The Dynamics of Determinants Making Stock Investment Decisions: Does Investor Sentiment Possess Significant Influence? - Nicola, Nicola; Christian, Michael (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
In 2024, the Composite Stock Price Index underwent a significant fall due to multiple domestic and worldwide issues. Numerous prior research have investigated financial behavioral elements as a connection in investment decisions; nevertheless, this study presents originality by concentrating on these factors that exert a direct influence. This study analyzes the financial behavioral aspects that affect stock investment decisions in Indonesia, particularly in the Jakarta region. This research employs a quantitative approach via a questionnaire survey to gather primary data, which is subsequently analyzed using SmartPLS. This discovery alters the current paradigm. This study revealed that, despite the common belief that investor sentiment affects investing decisions, the findings indicate that investor sentiment does not exert a substantial influence. This study demonstrated that, contrary to numerous other studies indicating that investor sentiment affects investment decisions, investor sentiment does not exert a substantial influence. This discovery contests the current paradigm and demonstrates that elements such as economic fundamentals, market volatility, and individual investor traits are more influential in investment decision-making. This study encourages research on other factors affecting Indonesian stock market investment decisions. Future research should include more factors and widen the study region to better understand investment behavior.